2010
DOI: 10.1002/ajmg.a.33779
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and natural history of mucopolysaccharidosis type III in France and comparison with United Kingdom and Greece

Abstract: Sanfilippo syndrome, or mucopolysaccharidosis type III (MPSIII) is a lysosomal storage disease with predominant neurological manifestations in affected children. It is considered heterogeneous with respect to prevalence, clinical presentation, biochemistry (four biochemical forms of the disease referred to as MPSIIIA, B, C, and D are known), and causative mutations. The perspective of therapeutic options emphasizes the need for better knowledge of MPSIII incidence and natural history. We performed parallel ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
204
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(234 citation statements)
references
References 47 publications
(59 reference statements)
17
204
0
9
Order By: Relevance
“…Among all types of mucopolysaccharidoses, Sanfilippo disease (MPS type III) is the most common entity. 1 Speech delay was the most frequent clinical symptom before diagnosis [2][3][4] and coarse facial features were present before diagnosis in 78% of MPS III patients. 5 Unlike Hurler syndrome (MPS I) or Hunter syndrome (MPS II), patients with Sanfilippo disease often have early very mild coarse facial features.…”
Section: Discussionmentioning
confidence: 99%
“…Among all types of mucopolysaccharidoses, Sanfilippo disease (MPS type III) is the most common entity. 1 Speech delay was the most frequent clinical symptom before diagnosis [2][3][4] and coarse facial features were present before diagnosis in 78% of MPS III patients. 5 Unlike Hurler syndrome (MPS I) or Hunter syndrome (MPS II), patients with Sanfilippo disease often have early very mild coarse facial features.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal behaviors have been described as aggressive and hyperactive with sleep disturbance (Cleary and Wraith 1993;Valstar et al 2011;Meyer et al 2007;Fraser et al 2002). Autistic-like symptoms and loss of normal fear have also been described (Heron et al 2011). In a recent study, (Heron et al 2011) found the average lifespan for MPS IIIA to be 15.4 years (Heron et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…В работах зарубежных [14,15,17], а также российских авторов показано [6,16], что самая высокая доля больных с эпилепсией наблюдается при нейроно-патических типах МПС II и III. По данным международных и отечественных исследователей, среди больных МПС II распространенность эпилепсии колеблется в диапазоне от 13 до 34% [17][18][19], с более высоким процентом (от 28 до 63%) у больных с нейронопатическим феноти-пом [20][21][22]; средний возраст появления эпилептиче-ских приступов -~10 лет [16][17][18]. По данным I.…”
Section: распространенность эпилепсии при мукополисахаридозахunclassified